Post-Covid effects on respiratory mechanics, pulmonary function, response to physical exercise and quality of life (Research, Society and Development, 2022)
Introduction: In December 2019, the World Health Organization (WHO) was informed about some cases of pneumonia of unknown cause detected in the city of Wuhan, China. After researches and investigations, the causative agent of COVID-19 was detected: the SARS-CoV-2 virus. Despite the large number of reported cases of COVID-19, the sequels left by the disease are still poorly understood. Therefore, this study aimed to evaluate the respiratory mechanics, pulmonary function, response to physical exercise and quality of life of individuals who were contaminated by SARS-CoV-2. Methods: 15 participants underwent assessment of vital signs, maximal inspiratory and expiratory pressures (MIP; MEP) (Ger-Ar® Manovacuometer), thoracoabdominal mobility (cirtometry), peak expiratory flow (PEF) (Peak Flow NCS®), pulmonary function (Microquark® Spirometer), 6-minute walk test (6MWT), Medical Research Council (MRC) questionnaire and quality of life questionnaire (SF-36).  Results: There was a decrease in MIP, MEP, PEF, abdominal expansion, and distance covered in the 6MWT when compared to predicted values; Regarding cardiovascular responses on the 6MWT, SF-36 questionnaire, MRC dyspnea scale and pulmonary function, no significant changes were observed.